Strategi Pengembangan Usaha Dengan Metode Analisis SWOT Pada Home Industri Wen-Dang Jahe Di Kabupaten Kukar - Mardiyana Mardiyana (Jurnal Administrasi Bisnis Fisipol Unmul, 2022)
The study aims as a consideration for a strategy that matches application with mingidentify internal factor and externally at Home Industrial Wen-Dang in Kukar district. Ingathering primary data is conduction through deep interviews of informants, and the informants in the study are business owners, sellers and consumers while the skunders are gathered throught library studies, journal-journal research and general images of objeck research, a vision and mission of a company acquired directly from wenker home industrie’s. The method used is a descriptive method of paster-qualitative. Results derived from this research a workable home strategy Wen-Dang ginger Industry in kukar district maintains its trademark produk flavor and improved product quality in order to increase market demand and expand consignment sales. The internal factor is strength of Wen-Dang ginger has P-IRT clearance, Wen-dang ginger has halal MUI, Have good quality (both taste and packaging), Wen-Dang ginger products in kukar county are worth up to 6 months, reasonable price. Weaknesses of Home industry marketing Wen-Dang ginger in kukar district is just offline, just having one type product, has no target of production, has no target sale, managed with only family members. The exsternal factor is Opportunity of user the internet as a promotional medium, public trust in the product, have regular customers, provide convenience for consumers, people’s lifestyles consume natural product as the main choice. Threat of unstable raw material prices, there is a shortage of raw material, many substitute products with various variants, there are other products that are cheaper, emergence of new competitors.